2000
DOI: 10.1159/000007754
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gastrin-Releasing Peptide on Intestinal Microcirculation after Ischemia-Reperfusion in Rats

Abstract: We investigated the effect of gastrin-releasing peptide (GRP) and its antagonist RC-3095 on intestinal microcirculation after ischemia-reperfusion. Intestinal ischemia was induced in female Wistar rats by occlusion of the superior mesenteric artery for 40 min. Ten minutes prior to reperfusion, infusion of GRP or RC-3095 was started. A jejunal segment was exteriorized and the microhemodynamics of the mucosa and submucosa were examined by intravital microscopy and compared both with normal and ischemic controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
7
0
4
Order By: Relevance
“…An alternative explanation might be the reduction of endotoxemia, which is associated with generation of oxygen free radicals via a xanthine oxidase-dependent pathway [43]. Moreover, improvement of intestinal and liver microcirculation by regulatory peptides [44] prevents hypoxia and energy depletion that leads to oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation might be the reduction of endotoxemia, which is associated with generation of oxygen free radicals via a xanthine oxidase-dependent pathway [43]. Moreover, improvement of intestinal and liver microcirculation by regulatory peptides [44] prevents hypoxia and energy depletion that leads to oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Heuser et al [26]could show that GRP in pharmacological doses has a protective effect on intestinal microcirculation during reperfusion. Further investigations with the GRP antagonist RC-3095 suggested that endogenous GRP may play a decisive role in the maintenance of microvascular integrity during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, numerous experimental studies have demonstrated the protective effect of BBS and NTS against diverse types of intestinal injury, such as administration of elemental diets or methotrexate, induction of chemical colitis, burns, radiation therapy, ischemia/reperfusion and small bowel resection [3][4][5][6][7][8][9] . However, the molecular and cellular mechanisms implicated in their intestinal mucosa-healing effect remained unresolved for a long period.…”
Section: To the Editormentioning
confidence: 99%